ASUHAN KEPERAWATAN JIWA PADA NY. W DENGAN ISOLASI SOSIAL DI WILAYAH PUSKESMAS SINDANGKASIH KABUPATEN CIAMIS - Asep Riyana; Resma, Efany (Poltekkes Kemenkes Tasikmalaya, 2024)
The high number of mental disorders in Indonesia, especially in West Java, is around 2,465,835.6 people (5.0% of the total population of West Java in 2018). According to data from the Sindangkasih Health Center, the number of cases of severe mental disorders, namely schizophrenia, was 43 cases out of 76 or (57%) of all existing mental disorders. to gain real experience in carrying out direct and comprehensive nursing care. The concept that underlies the research is Schizophrenia and Social Isolation.Schizophrenia is a serious mental illness characterized by incoherent thoughts, strange behavior, strange speech, and hallucinations, such as hearing voices (APA, 2020 in Hadiansyah & Pragholapati, 2020). This scientific paper design uses descriptive qualitative research. Nursing care used includes assessment, nursing diagnosis, planning, implementation, and evaluation. The results of the assessment obtained 3 nursing problems which were arranged into 3 nursing diagnoses, namely Social Isolation, Low Self-Esteem, Hallucination Sensory Perception Disorders. The author plans according to client problems. Efforts made at the implementation stage are providing an implementation strategy by involving the active role of the client and family. The results of the evaluation show that the specific goals set in the planning can be achieved and the main problem of social isolation is partially resolved, marked by the client being able to socialize with other people